LiNbO3 electronic structure: Many-body interactions, spin-orbit coupling, and thermal effects - Riefer, Arthur; Friedrich, Michael; Sanna, Simone; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The influence of electronic many-body interactions, spin-orbit coupling, and thermal lattice vibrations on the electronic structure of lithium niobate is calculated from first principles. Self-energy calculations in the GW approximation show that the inclusion of self-consistency in the Green function G and the screened Coulomb potential W opens the band gap far stronger than found in previous G0W0 calculations but slightly overestimates its actual value due to the neglect of excitonic effects in W. A realistic frozen-lattice band gap of about 5.9 eV is obtained by combining hybrid density functional theory with the QSGW0 scheme. The renormalization of the band gap due to electron-phonon coupling, derived here using molecular dynamics as well as density functional perturbation theory, reduces this value by about 0.5 eV at room temperature. Spin-orbit coupling does not noticeably modify the fundamental gap but gives rise to a Rashba-like spin texture in the conduction band.